To simplify the expression \( \sqrt[3]{40} \), we can break it down into its prime factors:
\[ 40 = 8 \times 5 = 2^3 \times 5 \]
Now, we can apply the property of cube roots:
\[ \sqrt[3]{40} = \sqrt[3]{8 \times 5} = \sqrt[3]{8} \times \sqrt[3]{5} \]
Since \( \sqrt[3]{8} = 2 \), we have:
\[ \sqrt[3]{40} = 2 \times \sqrt[3]{5} \]
Thus, \( \sqrt[3]{40} \) can be expressed as:
\[ 2 \sqrt[3]{5} \]
Looking at the provided options, the expression that corresponds to \( 2 \sqrt[3]{5} \) is:
b. \( 2 , \text{cube root of} , 5 \).